PERILAKU PENJAMAH MAKANAN DALAM PENERAPAN PERSONAL HYGIENE DI INSTALASI GIZI RSJ MENUR SURABAYA TAHUN 2022 - Athaya Rahma Dewi; Hadi Suryono; Setiawan (Jurnal Higiene Sanitasi, 2022)
The application of hygiene for food handlers is very important to create food safety. A preliminary survey conducted at the Nutrition Installation of Menur Mental Hospital in Surabaya found that food handlers still did not apply personal hygiene optimally. The purpose of this study was to describe the behavior (knowledge, attitudes, facilities and infrastructure, and family support) of food handlers in the application of personal hygiene at the Nutrition Installation of Menur Mental Hospital in 2022. This type of research was descriptive with a cross-sectional approach. The population was 18 workers and used total sampling. Data collection techniques using questionnaires and interviews. The variables in this study include knowledge, attitudes, facilities and infrastructure, and family support. The results showed that the application of personal hygiene for food handlers at the Nutrition Installation of RSJ Menur Surabaya for knowledge included in the good category 94% and the sufficient category 5.6%. The attitude included in the good category were 83.3% and the sufficient category was 16.7%. All of the facilities and infrastructure in the adequate category, namely 100%. Family support was include in the category of suporting 88.9% and not suporting 11%. It is hoped that the Hospital, especially the Nutrition Installation, will routinely provide education about the stages of washing hands with soap and complete the instructions for the stages of washing hands. For other researchers, they can develop this research related to the relationship between family support and the level of economic income.